PROGRAM PENDIDIKAN SEKS UNTUK MENINGKATKAN PROTEKSI DIRI DARI EKSPLOITASI SEKSUAL PADA ANAK USIA DINI - Zarina Akbar; Felianti Mudzdaliffah (Perspektif Ilmu Pendidikan, 2012)
Sexual violence against the children often occurs as they have not got sex education. Therefore, sex education should be provided to the early-age children and a research is conducted to find out the result. This research aims at knowing the children’s ability to protect themselves from sexual violance. The research conducted at Ar-Rachman Kindergarten, South Jakarta in November 2011 employed quantitative quasi-experiment. The analysis indicates significant difference in the score between pre-test and post-test of the experiment group. Based on the finding, the research concludes that there is a significant difference in self protection ability for the student having achieved sex education program compared to those who have not. The research recommend sex education should be provided for early-aged children to minimize sexual violence.